ROBUSTNESS OF THE BANK RESOLUTION FRAMEWORK IN THE EUROPEAN UNION - Jan Pys (Copernican Journal of Finance & Accounting, 2017)
The purpose of this article is to identify the key elements of resolution framework under the Single Resolution Mechanism (SRM) and to assess the robustness of the bank resolution framework in the European Union (EU). The 2007–2009 global financial crisis exposed number of weaknesses in the banking sector. It also showed the unpreparedness of the European governments in dealing with failing banks and the possible negative consequences it can have on the wider economy. As result, in order to save the economy from even deeper crisis, governments in many European countries had no other choice than to bail-out the “too-big-to-fail” banks using taxpayers’ money. Post-crisis, banking regulators recognised the need for a broader reform and creation of a formalized resolution framework which would allow for efficient resolution of troubled banks with no or limited use of public funds. The resolution proceedings are complex procedures, which need to balance the interest of the different bank stakeholders such as: shareholders, debt holders, regulatory and supervisory authorities, governments and many others. In the EU, the SRM was put in place together with Bank Recovery and Resolution Directive (BRRD) to address the issues identified during the crisis. This article is an attempt to demonstrate that the new European resolution framework contains provisions and tools that may limit the use of public funds in resolution of failing banks. The outcome provides a framework for further research focused on better understanding of the trade-offs in resolution framework and measuring the efficiency of bank resolution in the EU.